Chilling temperature and low moisture content to keep soybean grain quality during storage - Rigueira, Roberta J. A.; Filho, Adilio F. Lacerda; Lazzari, Flavio A.; Marques, Kaio K. M.; Coelho, Marcelo P. (Julius-Kühn-Archiv, 2018)
Soybeans are used as food, feed, oil and fuel. Losses may happen at harvesting, transportation, and mainly during storage. Moisture content (MC %) and temperature (T °C) of the soybean grain mass during storage are the main factors affecting quality, quantity and value of the product by favoring the development of microorganisms and insects. Large grain chillers have been used to maintain soybean quality and reduce insect infestation during storage. To evaluate the effect of MC and temperature on the quality parameters of soybean seeds, samples were stored at 58±2% RH, with five different MCs, at 15 °C (chilling temperature) and 30 °C (average temperature inside silos in Brazil) for 180 days. The following was observed: reduction in the MC at higher temperature; the weight of soybeans was maintained at either temperature when the MC was at about 12%; MC above 14% reduced the weight value independent of storage temperature; at 15°C the weight of 1,000 seeds was maintained during storage; low MC and temperature kept germination and vigor of the seeds at high rates; low MC and temperature reduced electrical conductivity; there was no noticeable influence of the storage temperature, regardless of the MC of the beans, on the free fatty acid content. In general, quality attributes tend to be reduced during storage, being more remarkable at higher temperature and MC of the seeds. In conclusion, the temperature of 15ºC, which simulates grain cooling conditions, favors the maintenance of quality, quantity and value of soybean for long-term storage.